2015
DOI: 10.1093/nar/gkv601
|View full text |Cite
|
Sign up to set email alerts
|

Development of an intein-mediated split–Cas9 system for gene therapy

Abstract: Using CRISPR/Cas9, it is possible to target virtually any gene in any organism. A major limitation to its application in gene therapy is the size of Cas9 (>4 kb), impeding its efficient delivery via recombinant adeno-associated virus (rAAV). Therefore, we developed a split–Cas9 system, bypassing the packaging limit using split-inteins. Each Cas9 half was fused to the corresponding split-intein moiety and, only upon co-expression, the intein-mediated trans-splicing occurs and the full Cas9 protein is reconstitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
226
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 301 publications
(243 citation statements)
references
References 44 publications
3
226
0
2
Order By: Relevance
“…These variants, including an intein-inactivated Cas9 system (Davis et al, 2015) and a small molecule-dimerized split Cas9 system (Zetsche et al, 2015b), have been shown to substantially improve genome editing specificity in mammalian cells compared with wild-type Cas9 by carefully controlling the temporal window within which active Cas9 is generated so that less active Cas9 is present after modification of the on-target loci is complete (Figure 2g,h). Similar systems, such as light-activated Cas9 variants (Nihongaki et al, 2015a;Hemphill et al, 2015;Jain et al, 2016), split Cas9 variants (Truong et al, 2015;Wright et al, 2015), small-molecule induction of Cas9 (Dow et al, 2015), and an engineered allosterically regulated Cas9 (Oakes et al, 2016) could also be used to reduce off-target genome editing following these same principles.…”
Section: Improving the Dna Specificity Of Crispr-based Agentsmentioning
confidence: 99%
“…These variants, including an intein-inactivated Cas9 system (Davis et al, 2015) and a small molecule-dimerized split Cas9 system (Zetsche et al, 2015b), have been shown to substantially improve genome editing specificity in mammalian cells compared with wild-type Cas9 by carefully controlling the temporal window within which active Cas9 is generated so that less active Cas9 is present after modification of the on-target loci is complete (Figure 2g,h). Similar systems, such as light-activated Cas9 variants (Nihongaki et al, 2015a;Hemphill et al, 2015;Jain et al, 2016), split Cas9 variants (Truong et al, 2015;Wright et al, 2015), small-molecule induction of Cas9 (Dow et al, 2015), and an engineered allosterically regulated Cas9 (Oakes et al, 2016) could also be used to reduce off-target genome editing following these same principles.…”
Section: Improving the Dna Specificity Of Crispr-based Agentsmentioning
confidence: 99%
“…An alternative strategy to control the binding of Cas9 to its target sequence relies on intein-mediated splicing (Davis et al, 2015;Truong et al, 2015). Designs with intein in the reading frame of fulllength Cas9 or fused to both fragments of split-Cas9 have been used.…”
Section: Class II -Indirect Effector Recruitmentmentioning
confidence: 99%
“…Designs with intein in the reading frame of fulllength Cas9 or fused to both fragments of split-Cas9 have been used. In both cases, after intein transsplicing is induced full-length functional Cas9 is obtained (Davis et al, 2015;Truong et al, 2015). An other, less common approach, is to use Cas9 inactive due to caging of lysine residues necessary for Cas9 function (Hemphill et al, 2015).…”
Section: Class II -Indirect Effector Recruitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, AAV is limited by the small size of the transgene that can be accommodated. There are a number of approaches to this problem, including delivering Cas9 and gRNAs in separate AAV vectors [68], splitting the Cas9 enzyme into halves that are delivered separately [69], or using a split-Cas9 with split-inteins and intein-mediated trans-splicing reconstitution of the full-length Cas9 protein [70]. Ran et al [71] reported that Cas9 from Staphylococcus aureus (SaCas9) is able to edit with similar efficiency to Cas9 from Streptococcus pyogenes but is > 1 kb shorter.…”
Section: Delivery Of Crispr/cas9mentioning
confidence: 99%